2017
DOI: 10.1108/jsbed-01-2017-0020
|View full text |Cite
|
Sign up to set email alerts
|

Internationalization and innovation in nascent companies: does gender matter?

Abstract: Purpose The purpose of this paper is to explore the competitiveness of women entrepreneurs in terms of internationalization and innovation. Supported by a resource-based framework of early internationalizing firms, the authors investigated multiple conditions for the relationship between internationalization and innovation relative to gender in nascent companies. Design/methodology/approach For this purpose, the authors used survey data related to entrepreneurial activity in 50 countries from the Global Entr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
50
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(62 citation statements)
references
References 79 publications
7
50
0
5
Order By: Relevance
“…For example, women-owned firms involved in the global marketplace have greater revenues, are more optimistic about their business prospects, and are more focused on business expansion compare to women-owned firms doing business domestically [6,44]. However, women entrepreneurs' journey in international trade is not the same as for their counterparts [2,10,45]. Muñoz-Bullón, Sánchez-Bueno, and Vos-Saz [46] found that entrepreneurial personality traits, such as proactiveness, risk-taking, and innovativeness, have a significant influence on the entrepreneur's entry into foreign markets.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 4 more Smart Citations
“…For example, women-owned firms involved in the global marketplace have greater revenues, are more optimistic about their business prospects, and are more focused on business expansion compare to women-owned firms doing business domestically [6,44]. However, women entrepreneurs' journey in international trade is not the same as for their counterparts [2,10,45]. Muñoz-Bullón, Sánchez-Bueno, and Vos-Saz [46] found that entrepreneurial personality traits, such as proactiveness, risk-taking, and innovativeness, have a significant influence on the entrepreneur's entry into foreign markets.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Moreover, Wallace [37] argued that the strategic framework established by previous researchers has failed to tackle gender inequalities due to the dominant use of 'rational economic man (REM)' discourse in policy and mainstream business arena. Assessing women entrepreneurs' performances by using a gender-blind approach portrays a picture that women are less competitive in international business development and growth, as found in Alves et al [2]. Such findings would create fears for women entrepreneurs and discourage them from the advancement in business rather than help them to build confidence.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations